Efektivitas Penegakan Hukum terhadap Tindak Pidana Pencurian Kendaraan Bermotor (CURANMOR) di Wilayah Hukum Polres Buleleng - Gede Widi Bayu Suta; Putu Riski Ananda Kusuma; I Gede Partama (Jurnal Hukum dan Sosial Politik, 2026)
Motor vehicle theft remains a prevalent criminal offense within the jurisdiction of the Buleleng Regional Police, necessitating optimal law enforcement efforts. This study aims to examine the implementation of law enforcement against vehicle theft while mapping the factors that influence its efficacy. Utilizing an empirical legal research method with a sociological approach, data were gathered through interviews with investigators from the Criminal Investigation Unit of the Buleleng Regional Police and a review of relevant literature. The qualitative data analysis was guided by Soerjono Soekanto's legal effectiveness theory. The findings indicate that the police tackle vehicle theft through both preventive and repressive strategies, including investigations, offender apprehensions, area patrols, and public legal awareness campaigns. The success of law enforcement is highly contingent upon legal substance, law enforcement commitment, facility availability, public participation, and local legal culture. Consequently, stronger inter-agency synergy, enhanced supporting facilities, and increased public legal consciousness are required to suppress vehicle theft rates in Buleleng Regency.